The Development of Economic Analysis in Uzbekistan and Some Features in the Digital Economy - Fozilov Ibrokhimjon Rakhimovich; Fozilov Hayotjon Rakhimovich (Zien Journals, 2022)
As a result of the development of economic reforms in our country, as in all areas of socioeconomic development, commendable achievements have been achieved in the field of science. In particular, in the context of the digital economy, the attitude to economic analysis began to change radically. The role of this science in accelerating the economic reforms carried out in Uzbekistan is very important, since in practice the analysis is reflected as one of the economic pillars. It should be noted that the purpose of economic analysis is to study the activities of an economic entity, its further development, improvement, full use of available opportunities, dissemination of achievements and causes of shortcomings and assistance in their elimination. The scientific article examines in detail the economic analysis, its goals and objectives, its role in the management of economic entities and in the conditions of the digital economy, its current state and its improvement.
Keywords: Digital economy; its content; economic analysis; its significance and history; goals and objectives of analysis